Aggressività e istinto di morte. Il rapporto sadomasochistico con l’oggetto e l’eliminazione dell’oggetto (riferimenti al transfert e al setting) - Fagioli, Massimo (Il sogno della farfalla, 2022)
This article, already published in 1972 in the “Psychoanalysis Journal”, summarizes the seminar held by Massimo Fagioli during the 11th Scientific Congress of the Italian Psychoanalytic Society (Bologna, 10-11 June 1972). In the author’s speech and the debate that followed, the foundation of this theory and its psychotherapeutic praxis, specifically related to the relation of transfer-countertransference and setting were clearly outlined. Furthermore, the concept of disappearance phantasy became at the core of the discussion of the authors with other clinicians.